PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN PADA KETEPATWAKTUAN LAPORAN KEUANGAN - Ferdina, Ni Wayan Ajeng; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2017)
Information in the financial statements is used for decision making purposes and therefore timeliness of financial statements is very important. The purpose of this research is to analyze factors that affect the timeliness of financial statements of companies in the manufacturing sector listed in Indonesia Stock Exchange. Variables that consist of profitability, leverage, liquidity, and firm size are factors that are tested in this research. By the method of purposive sampling, this research uses 336 samples during the period of 2012-2015. Methods of data collection in this research is non-participant observation and the technique of data analysis is logistic regression. The result of the analysis shows that profitability and firm size have positive effect while leverage has negative effect. Liquidity has no effect in the timeliness of financial statement.
Keywords: timeliness, profitability, leverage, liquidity, firm size